EAU-ESPU guidelines recommendations for daytime lower urinary tract conditions in children - Tekgul, Serdar; Stein, Raimund; Bogaert, Guy; Undre, Shabnam; Nijman, Rien J. M.; Quaedackers, Josine; 't Hoen, Lisette A.; Kocvara, Radim; Silay, Mesrur Selcuk; Radmayr, Christian; Dogan, Hasan Serkan (European journal of pediatrics, 2020)
The objective is to review the literature related to lower urinary tract (LUT) conditions in children to conceptualize general practice guidelines for the general practitioner, pediatrician, pediatric urologist, and urologist. PubMed was searched for the last 15-year literature by the committee. All articles in peer-review journal-related LUT conditions (343) have been retrieved and 76 have been reviewed extensively. Prospective trials were few and the level of evidence was low. Most of the recommendations have been done by committee consensus after extensive discussion of literature reports. History taking is an integral part of evaluation assessing day- and nighttime urine and bowel control, urgency, and frequency symptoms. Exclusion of any neurogenic and organic cause is essential. Uroflowmetry and residual urine determination are recommended in all patients to evaluate bladder emptying. Urodynamic studies are reserved for refractory or complicated cases. Urotherapy that aims to educate the child and family about bladder and bowel function and guides them to achieve normal voiding and bowel habits should initially be employed in all cases except those who have urinary tract infections (UTI) and constipation. Specific medical treatment is added in the case of refractory overactive bladder symptoms and recurrent UTIs. Conclusion: Producing recommendations for managing LUTS in children based on high-quality studies is not possible. LUTS in children should be evaluated in a multimodal way by minimal invasive diagnostic procedures. Urotherapy is the mainstay of treatment and specific medical treatment is added in refractory cases.What is Known:center dot Symptoms of the lower urinary tract may have significant social consequences and sometimes clinical morbidities like urinary tract infections and vesicoureteral reflux. In many children, however, there is no such obvious cause for the incontinence, and they are referred to as having functional bladder problems.What is New:center dot This review aims to construct a practical recommendation strategy for the general practitioner, pediatrician, pediatric urologist, and urologist for LUTS in children. Producing recommendations for managing LUTS in children based on high-quality studies is not possible. LUTS in children should be evaluated in a multimodal way by minimal invasive diagnostic procedures. Urotherapy is the mainstay of treatment and specific medical treatment is added in refractory cases.
Gesehen am 12.05.2021